E-commerce is Paralyzing Distribution Contracts in Indonesia - Fransiscus, Risza (Global Legal Review, 2022)
The rapid development of digital technology has boosted the growth of trading systems in the world through the internet (e-commerce). The proliferation of this technology is always faster than the availability of laws and regulations governing its implementation. Although a bit late, the Government of the Republic of Indonesia has made regulations for the implementation of e-commerce through the issuance of Government Regulation No. 80 of 2019 concerning Trading Through Electronic Systems which was promulgated on November 25, 2019 (GR 80 2019). The establishment of GR 80/2019 was mandated by Article 65 of the Indonesian trade regulation. This GR 80/2019 is to build 'consumer trust' and 'consumer confidence' by ensuring consumer protection and fair business competition. In addition, this regulation ensures the creation of a secured e-commerce ecosystem by encouraging increased activities and growth in trade and the e-commerce industry[1].This GR 80/2019 provides a wide space for individuals or companies desiring to become e-commerce business actors. However, this definition of E-commerce Business Actor does not provide any limitations for distribution business actors being bound by distribution contracts under laws and regulations in the distribution sector. The absence of restrictions for Distribution Business Actors to become E-commerce Business Actors can create unfair competition for the Indonesian trade, particularly in the distribution channels of goods in Indonesia. This occurs due to the Distribution Business Actors (manufacturers, distributors, sub-distributors, agents, sub-agents) may compete among themselves, thus damaging the distribution channels which have been stipulated by the government through laws and regulations since 1977. Moreover, no provision in the GR 80/2019 requires E-commerce Business Actors to comply with the laws and regulations in the distributions sector. Uniquely, the Government of the Republic of Indonesia also continues to issue laws and regulations in the distribution sector even after the promulgation of GR 80/2019.After the ratification of Law No.11 of 2020 concerning Job Creation, the government issued government regulation No.29 of 2021 concerning the implementation of the Trade Sector and then 2 months later followed by the establishment of its implementing regulation i.e. Minister of Trade Regulation No.24 of 2021 concerning Agreements for the Distribution of Goods by Distributor or Agent. Conflict of implementation between GR 80/2019 and Chapter IV (distribution of goods) in GR 80/2019 will gravely paralyze the business of distribution of goods and/or services conducted by domestic business actors in Indonesia.The writing of this journal restricts Distribution Business Actors as (i) foreign principals (principal producers or principal suppliers) having registered address in other countries or Direct Investment Companies in Indonesia (PMA); and (ii) distribution business channels in Indonesia in the form of distributors, sub-distributors, agents, and sub-agents, each of them is legally domiciled in Indonesia.[1])  Press Conference of Public Relations of Ministry of Trade, “PP No.80 Tahun 2019: Pemerintah Lahirkan Peraturan Pemerintah tentang Perdagangan Melalui Sistem Elektronik”, 10 of December 2019, officially published at https://kemendag.go.id>article_uploads.